Veit Harlan - Noack, Frank, 1961- (Screen classics, 2016)
Veit Harlan (1899-1964) was one of Germany's most controversial and loathed directors. The first English-language biography of the notorious director, Veit Harlan presents an in-depth portrait of the man who is arguably the only Nazi filmmaker with a distinct authorial style and body of work.